THE CHARACTERISTICS OF A GOOD ENGLISH TEACHER AS PERCEIVED BY SECONDARY SCHOOL STUDENTS IN NURUL JIHAD TEMBILAHAN HULU - Guspita, Anggi Riani; Mustajib, Agus; Ardian, Edi (Program Studi Pendidikan Bahasa Inggris, 2023)
This study aims to find the characteristics of a good English teacher. The aim is to find out students' perceptions of a good English teacher in terms of technical knowledge, pedagogic skills, interpersonal skills and personal qualities. This research includes descriptive research. Data was taken by observation, interviews and then analyzed qualitatively using a questionnaire. The findings of this study indicate that the characteristics of good teachers with respect to technical knowledge are mastering English, understanding teaching methods, being able to teach clearly, understanding students' abilities, and understanding teaching methods. The characteristics of a good English teacher with respect to interpersonal skills are teachers who are relaxed, humorous, cooperative, and able to win over students. The characteristics of a good teacher in terms of pedagogy are teachers who have teaching skills, use interesting media and a variety of techniques, are creative and innovative in designing material, understand students' needs, motivate students to be enthusiastic about learning English. The characteristics of a good English teacher with respect to personal qualities are a good figure, kind hearted and obedient to worship, discipline, patience, having good habits, attitudes and behavior, always maintaining quality and enthusiasm in teaching. The results of the in-depth open questionnaire show that students' perceptions of the characteristics of a good English teacher are very tedious and cognitive.